Blood presure variability in patients with obstructive sleep apnea syndrome and heart failure with preserved ejection fraction. - I. O. Andreieva; D. P. Myrnyi; M. M. Surmilo (Medičnì Perspektivi)
The aim of the study was to investigate the features of daily blood pressure changes in patients with obstructive sleep apnea syndrome (OSAS) and heart failure with preserved ejection fraction based on the data of daily blood pressure monitoring. Materials and methods. 86 patients with OSAS and HFpEF (group 1), 74 patients with HFpEF without OSAS (2nd group) and 52 patients with OSAS and without HF (group 3) were examined. All participants of the study underwent cardio-respiratory monitoring, ABPM, echocardiography, NT-proBNP. Results. SABP and DABP in patients with HFpEF and OSAS were generally higher in the day and night than in comparison groups. "Non-dipper" dominated among the pathological daily profiles. As results of the multivariate regression analysis, it was found that the level of SABP at night was determined by IAH (β=0,386, p<0,05) and MeanSaO2 (β=0,339, p<0,05). The DABP level at night was determined by the IAH (β=0.412, p<0.05). Conclusions. Patients with OSAS and HFpEF have insufficient reduction in blood pressure at night and greater variability of blood pressure overnight. With the increase of OSAS severity more often daily profiles "non-dipper" and "night-peaker" are recorded, the variability of blood pressure increases. When performing a multivariate regression analysis, it was found that the level of SABP at night was determined by IAH (β=0,386, p<0,05) and MeanSaO2 (β=0,339, p<0,05); DABP level at night was determined by the IAH (β=0,412, p<0,05).